Lsm12 is an NAADP receptor and a two-pore channel regulatory protein required for calcium mobilization from acidic organelles - Jiyuan Zhang; Xin Guan; Kunal Shah; Jiusheng Yan (Nature Communications, 2021)
Nicotinic acid adenine dinucleotide phosphate (NAADP) potent Ca2+ mobilizing second messenger which uniquely triggers Ca2+ release from acidic endolysosomal organelles. Here the authors identify Lsm12 as an NAADP receptor essential for NAADP-evoked Ca2+ release from lysosomes via NAADP binding on its Lsm domain.